2014
DOI: 10.1002/lary.25005
|View full text |Cite
|
Sign up to set email alerts
|

The utility of office‐based biopsy for laryngopharyngeal lesions: Comparison with surgical evaluation

Abstract: Office biopsy may offer early direction and avoid operative intervention in some cases; however, for suspected dysplastic or malignant lesions, direct microlaryngoscopy should be the standard of care to ensure adequate full-thickness sampling and staging. For benign pathology, office biopsy is a safe and viable alternative to direct microlaryngoscopy and biopsy/excision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
64
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(71 citation statements)
references
References 9 publications
5
64
1
1
Order By: Relevance
“…A recent study comparing in-office versus operating room biopsies for pathologic diagnosis found that in-office biopsies had 60% sensitivity and 87% specificity when compared to the final pathologic diagnosis obtained in the operating room. 14 There was especially poor sensitivity when diagnosing dysplasia and carcinoma in situ on in-office biopsies. 14 In these cases, pathologic diagnosis can be difficult secondary to the small biopsy size and limited depth inherent to in-office biopsies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study comparing in-office versus operating room biopsies for pathologic diagnosis found that in-office biopsies had 60% sensitivity and 87% specificity when compared to the final pathologic diagnosis obtained in the operating room. 14 There was especially poor sensitivity when diagnosing dysplasia and carcinoma in situ on in-office biopsies. 14 In these cases, pathologic diagnosis can be difficult secondary to the small biopsy size and limited depth inherent to in-office biopsies.…”
Section: Discussionmentioning
confidence: 99%
“…14 There was especially poor sensitivity when diagnosing dysplasia and carcinoma in situ on in-office biopsies. 14 In these cases, pathologic diagnosis can be difficult secondary to the small biopsy size and limited depth inherent to in-office biopsies. These factors may not impact bacterial culture results from biopsied tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, the biopsy of laryngopharyngeal lesions is performed under general anesthesia. Technological advancements in the types of transnasal endoscopes, instrument miniaturization, and topical anesthetic techniques have led to a shift in laryngeal management from the operation room to an office-based setting [68]. Since the introduction of fiberoptic laryngoscopy in the 1970s, lighting and imaging techniques have improved substantially [9].…”
Section: Introductionmentioning
confidence: 99%
“…In the latter, information from a chip in the distal tip of the endoscope is send to a video processor, which creates a digital image and enables high-resolution imaging. Furthermore, endoscopes can be equipped with a built in working channel for passage of a flexible biopsy forceps or a laser fiber [6, 8, 10]. This enables clinicians to perform surgical procedures under topical anesthesia in an office-based setting, such as laser surgery or flexible endoscopic biopsy (FEB).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation